Exploring the Relationship between Self-Efficacy and Academic Procrastination: A Study among Psychology Students - Natanael Ananda Putra; Christiana Hari Soetjiningsih (Bulletin of Counseling and Psychotherapy, 2023)
This research aims to determine the relationship between self-efficacy and academic procrastination in psychology students. The method used is quantitative with a correlational design. 165 students aged 18 to 25 years studying for a bachelor's degree at the Faculty of Psychology at Satya Wacana Christian University were research participants using the Accidental Sampling technique. Research measurements used the General Self-Efficacy Scale (GSES) developed by Schwarzer and Jerusalem and the Academic Procrastination Scale (APS) developed by McCloskey, with data analysis using product moment correlation from Karl Pearson. The research found a negative relationship between self-efficacy and academic procrastination in Satya Wacana Christian University psychology students. This is indicated by a correlation coefficient of -0.147 with a significance value of 0.030 (p<0.05). This means that the higher the level of self-efficacy in students, the lower the level of procrastination in students, and conversely, the lower the level of self-efficacy in students, the higher the academic procrastination behaviour in students. The results of this research can be used as material to make efforts to increase self-efficacy to prevent procrastination behaviour in students.